Molecular consequences of mitochondrial replacement may be masked from organismal traits in Tigriopus californicus - Jacob R. Denova; Ben A. Flanagan; Murad Jah; Scott L. Applebaum; Suzanne Edmands (PLoS ONE, 2025)
Mitochondrial replacement therapy (MRT) presents a promising preventative measure to combat mitochondrial diseases. However, the long-term consequences of disrupting mitonuclear coevolution at both the molecular and organismal levels remain understudied. Data on sex-specific effects are also lacking despite predictions that males may be especially vulnerable to mitochondrial replacement. To address this, we used backcrossed lines of the copepod Tigriopus californicus to produce offspring with nuclear genotype contributions from two populations and a mitochondrial genotype from a third, separate, population. When compared to hybrid controls with mitochondrial genotypes that matched the maternal nuclear genotype but not the paternal, these “three-parent offspring” did not significantly differ in lifespan or routine metabolic rate. While these organismal-level traits showed no effect, molecular metrics of mitochondrial health revealed consequences of mitochondrial replacement. Oxidative DNA damage, measured by 8-hydroxy-2’-deoxyguanosine content, was higher in three-parent offspring, and mitochondrial DNA content was lower than in hybrid controls. While differences between sexes were present in some traits, sex did not interact with mitochondrial replacement for any of these metrics. Although these results could be due either to donor mitochondrial DNA matching neither of the nuclear parents, or to deficits in the donor mitochondrial DNA itself, they highlight the importance of considering molecular level consequences of mitochondrial replacement that may be masked at the organismal level when evaluating the health impacts of this treatment.